2021
DOI: 10.1111/1468-5922.12683
|View full text |Cite
|
Sign up to set email alerts
|

Working online due to the COVID‐19 pandemic: a research and literature review

Abstract: Given the contemporary situation of many analysts in the world now being forced to work online due to the effects of the COVID‐19 pandemic, it is important to review the working online issue. Substantial debate over previous years has questioned whether a genuine analytic process can unfold through online work. This debate is reviewed with the conclusion that such a process is not necessarily precluded. Research outcomes are then reviewed to highlight those things that can facilitate positive outcomes when wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 63 publications
0
17
0
6
Order By: Relevance
“…The concerns reported by the selected articles mostly pertain to the ethical and legal aspects (often interlinked), which were already highlighted in previous literature before the pandemic [7], but nevertheless remain crucial. These included the following: informed consent (information about the risks and benefits of remote therapy) and autonomy (87%), patient privacy (78%) and confidentiality (57%), data protection and security (74.%), malpractice and professional liability/integrity (70%), equity of access (30%), quality of care (30%), the professional-patient relationship (22%), and the principle of beneficence or being disposed to act for the benefit of others (13%) [1,6,8,10,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Non-maleficence is the principle of preventing harm by actively promoting confidentiality, safety/safeguarding, and security.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concerns reported by the selected articles mostly pertain to the ethical and legal aspects (often interlinked), which were already highlighted in previous literature before the pandemic [7], but nevertheless remain crucial. These included the following: informed consent (information about the risks and benefits of remote therapy) and autonomy (87%), patient privacy (78%) and confidentiality (57%), data protection and security (74.%), malpractice and professional liability/integrity (70%), equity of access (30%), quality of care (30%), the professional-patient relationship (22%), and the principle of beneficence or being disposed to act for the benefit of others (13%) [1,6,8,10,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Non-maleficence is the principle of preventing harm by actively promoting confidentiality, safety/safeguarding, and security.…”
Section: Resultsmentioning
confidence: 99%
“…Commentary Italy [1] Law/regulations/legal issues (83%) stress the absence or variation of the rules among countries and the need for guidelines/best practices or standardization of telemedicine services. In particular, the questions raised regarded the following aspects: costs of services and reimbursement, insurance coverage, virtual prescription of medications, accreditation, licensing, commercialization, recording (as an area of controversy), and evaluation of the effectiveness of the services such as health outcomes and delivery, in terms of quality and cost, individual experience, program implementation, and key performance indicators [1,6,8,10,11,16,19,[21][22][23][24][27][28][29][30][31][32]34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sebagai perusahaan berbidang pelaksana konstruksi PT X umumnya perlu untuk berkomunikasi dan berbicara langsung dengan orang lain. Perusahaan dipaksa mampu "go digital" atau mengutamakan penggunaan teknologi terutama internet dalam operasional perusahaan secara online yang berkembang akibat pandemi COVID-19 (Merchant, 2021). Hal ini ditujukan supaya dikerjakan dari segala tempat, tidak hanya pada kantor saja.…”
Section: Innovatingunclassified
“…Despite reservations noted here, he concluded that actual physical presence in the same space is not required for various reasons, including the activity of mirror neurons to simulate communication at a distance, the presence of transference and countertransference reactions, and possibilities for unconscious communication and synchronicities (ibid., p. 322). Given the circumstances of the COVID‐19 pandemic, Merchant recently updated his review (2021), largely reinforcing his previous conclusions, although he makes further note of problematic aspects, such as online exhaustion, contraindications for treating severe personality disorders, and requirements for licensing, as well as multiple issues related to confidentiality of data and privacy.…”
mentioning
confidence: 92%